Randomized clinical trial comparing side to end vs end to end techniques for colorectal anastomosis. (November 2020) - Planellas, Pere; Farrés, Ramon; Cornejo, Lídia; Rodríguez-Hermosa, Jose Ignacio; Pigem, Anna; Timoteo, Ander; Ortega, Núria; Codina-Cazador, Antoni
Abstract: Background: Low anterior resection syndrome affects 60%–90% of patients with anastomoses after colorectal resection. Consensus regarding the best anastomosis is lacking. Objective: To compare outcomes after end-to-end versus side-to-end anastomoses. Design: Randomized clinical trial. Settings: University hospital (April 2016–October 2017). Patients: Patients aged ≥18 years with rectal or sigmoid adenocarcinoma. Interventions: Patients were randomized to undergo mechanical end-to-end or side-to-end (n = 33) anastomosis after laparoscopic resection. Main outcome measures: Primary outcome was to assess intestinal function (COREFO and LARS questionnaires) 12 months after surgery or ileostomy closure. Secondary outcomes were postoperative complications and intestinal function and quality of life (SF-36® questionnaire) at different time points after surgery or ileostomy closure. Results: No significant differences in intestinal function were observed between the two groups 12 months after surgery. Subanalysis of low-mid rectum tumors with end-to-end anastomosis yielded better function at 12 months. Postoperative complications did not differ between the two groups (p = 0.070), but reinterventions were more common in the side-to-end group (p = 0.040). Multivariate analysis found neoadjuvant treatment was independently associated with intestinal dysfunction at 12 months (β = 0.41, p = 0.033, COREFO; β = 0.41, p = 0.024, LARS). Conclusions: End-to-end anastomosis yielded low rates of severe complications and reintervention, as well as better intestinal function at 12 months in the subgroup with tumors in the low-mid rectum. Trial registration: clinicaltrials.gov identifier: NCT02746224. Highlights: The end-to-end group has had low re-interventions and low severe anastomotic leakage rates. 12 months after surgery or ileostomy closure 44.1% of patients had minor or major LARS. 53.3% of patients after low-mid rectal resection and 39.2% after high rectal or sigmoid resection had LARS. In low-mid rectal cancers, E-E had better functionality and quality of life one year after surgery or ileostomy reversal. In sigmoid and high rectal cancers, the E-E group had better quality of life at 12 months. Neoadjuvant treatment was an independent risk factor for worse intestinal dysfunction.